Analisis Kejadian Missfile Berkas Rekam Medis di Puskesmas Kalijaga - Tuti Herawati (Publikasi Indonesia, 2022)
From January to April 2021, 46 out of 200 medical record files were misplaced and misfiled, according to preliminary research conducted at the Kalijaga Health Center. Misplaced files and missfiles can interfere and cause delays in the patient care process, making new medical records other than missing medical records, making the contents of medical record files unsustainable. This study is designed to describe, prioritize causes, and schedule efforts to recover from erroneous file incidents using USG (Urgent, Severity, Growth) and brainstorming at the Kalijaga Health Center. This type of study uses qualitative and data collection through interviews, research, recordings, questionnaires, and brainstorming. The result is that the priority causes of the missfile problem are corrupt folders and stacked files that are not assigned to that folder. Efforts to overcome this problem are by replacing damaged folders, duplicating medical record folders, providing medical record folders sequentially, adding storage/filing shelves so that files do not pile up, separating inactive files.